A prospective longitudinal study of performance status, an inflammation-based score (GPS) and survival in patients with inoperable non-small-cell lung cancer - Forrest, L M (Nature Publishing Group, 2005)
The value of an inflammation-based prognostic score (Glasgow Prognostic score, GPS) was compared with performance status (ECOG-ps) in a longitudinal study of patients (n=101) with inoperable non-small-cell lung cancer (NSCLC). At diagnosis, stratified for treatment, only the GPS (HR 2.32, 95% CI 1.52–3.54, P<0.001) was a significant predictor of survival. In contrast, neither the GPS nor ECOG-ps measured at 3–6 months follow-up were significant predictors of residual survival. This study confirms the prognostic value of the GPS, at diagnosis, in patients with inoperable NSCLC. However, the role of the GPS and ECOG-ps during follow-up has not been established.